Comparative Analysis of Application Layer Protocols in EV Charging Stations: Evaluating HTTP, MQTT, and Websocket Performance Metrics - Argeshwara, Dityo Kreshna; Hadi, Mokh. Sholihul; Sendari, Siti; Irvan, Mhd (Association for Scientific Computing Electrical and Engineering, 2024)
In the burgeoning domain of electric vehicle (EV) technology, the advancement of supportive ecosystems plays a pivotal role. There is a marked global uptrend in the adoption of EVs, necessitating a robust network of EV charging stations. Integral to these stations is the infrastructure and the accompanying systems that govern their operation. With increased utilization, the exigency for expeditious service at these charging points escalates. This study undertakes a comparative analysis of three distinct data communication protocols at the application layer, specifically within the context of EV charging stations. The protocols scrutinized include Hypertext Transfer Protocol (HTTP), Message Queuing Telemetry Transport (MQTT), and Websocket. The benchmark for data transmission in this investigation is the delivery of energy information, adhering to the Open Charge Point Protocol (OCPP), a legally standardized open protocol. The data format employed is JavaScript Object Notation (JSON). Data transmission utilizing the three aforementioned protocols was intercepted and analyzed using Wireshark, a network protocol analyzer. Parameters such as latency (delay), jitter (variability of latency), and throughput (successful data delivery over a communication channel) were meticulously examined and subsequently represented graphically to enhance the interpretability of the network protocol performance. The findings reveal distinct transmission characteristics for each protocol, despite identical data payloads. HTTP exhibited the superior throughput, peaking at 31,621 bits per second (bps) during real-time data transmission. Conversely, MQTT demonstrated the most favorable latency and jitter metrics, both for real-time and periodic data dispatches. Websocket, however, registered the lowest throughput in real-time transmission, at 4,941 bps. These divergences underscore the importance of protocol selection based on specific performance criteria within EV charging station ecosystems.